Genome-wide characterization of copy number variants and their functional relevance in indigenous draught cattle of South Asia - Tafara Kundai Mavunga; Johann Sölkner; Gábor Mészáros; Maano Bryton Malima; Rudolf Pichler; Saravanan Ramasamy; Loku Galappattige Sampath Lokugalappatti; Ei Thandar; Menghak Phem; Farai Catherine Muchadeyi; Yosra Ressaissi; Mario Barbato; et al. (PLoS ONE, 2026)
Copy number variations (CNVs) are an important source of structural genomic variation and contribute to phenotypic diversity in cattle, including traits related to production, reproduction, and adaptation. In this study, we performed a genome-wide characterization of copy number variation regions (CNVRs) in Asian zebu cattle representing eight indigenous draught breeds traditionally used for ploughing, wet-field agriculture, and carting. CNVs were detected using two read-depth–based approaches, CNVnator and CNVcaller, which identified 7,705 and 5,640 CNVs, respectively. Integration of results from both methods using a 50% reciprocal overlap criterion yielded 6,143 CNVRs. The average number of CNVRs per breed ranged from 4,607–5,005, collectively covering approximately 6.23% of the autosomal genome. Of these, 2,697 CNVRs were shared across all breeds, whereas 190 CNVRs were breed specific. Population differentiation based on CNVs, estimated using pairwise V ST statistics, indicated that the Hallikar breed exhibited the highest average differentiation (0.07) relative to other breeds. A total of 4,868 genes overlapped with the identified CNVRs and were enriched for biological processes associated with immune regulation, metabolic function, and adaptive responses. Further comparison with cattle quantitative trait loci identified 65 unique QTLs, predominantly linked to carcass, fertility, reproduction, and growth traits. Overall, this study describes the genome-wide distribution and diversity of CNVRs in South Asian indigenous draught cattle and provides baseline genomic information for further investigations into structural variations relevant to breeding, management, and conservation.